Pengaruh Kecerdasan Emosi dan Efikasi Diri Terhadap Integritas Auditor - Masriani Mahyuddin; Eny Suprapti (SEIKO : Journal of Management & Business, 2023)
The profession of an auditor and a Public Accounting Firm (KAP) is a profession of public trust. Therefore, there are challenges in recruiting auditors. Good character qualifications possessed by a KAP auditor are integrity, emotional intelligence and self-efficacy. This consistency should be developed from within to outside oneself, not by coercion from outside into an auditor. The goal of this research is to empirically test emotional intelligence and self-efficacy that impact the integrity of the auditor. The data compilation method was carried out with existing delivered directly by the researcher. Submission of questionnaires to respondents and compilation of finalized questionnaires were taken out through KAP leaders or contact persons. This study tested the hypothesis using multiple linear reversion analysis methods to test the two hypotheses proposed. Data testing includes data quality testing, hypothesis testing, and classical assumption testing. The results of the regression test on the first hypothesis concluded that emotional intelligence has a significant influence on acceptable auditor integrity. The outcomes of the regression test on the second premise concluded that, theoretically and statistically, self-efficacy has a significant influence on the integrity of the auditor. Keywords: Emotional Intelligence, Self Efficacy, Auditors’ Integrity